ESTIMATION OF THE INCIDENCE OF INTRAOPERATIVE AWARENESS AND RECALL IN WAD MEDANI TEACHING HOSPITAL - SUDAN - AbdAlrazig Bushir Mohummed, AbdAllah; Mohammed, Dr. Nawal Mukhtar (Journal of Biomedical and Pharmaceutical Research, 2017)
The study was having been conducted in Wad Medani Teaching Hospital from March to September 2016. The objective of the study was to estimate the incidence of awareness under general anesthesia in Wad Medani Teaching Hospital for patients undergoing general anesthesia. The study designed as observational cross-sectional study; the data was collected by structural questionnaire filled during interview with the patients after their agreement. Cases of awareness and recall have been observed in 13.3 % among the study population. The study concluded that incidence of awareness under general anesthesia in Wad Medani Teaching Hospital is highly significant and more than the international practice and literature. It is also concluded that many factors caused this incidence of awareness include the decreased number of anesthesiologists , lack of proper funding for the hospital and anesthesia department , absence of anesthetic gases monitor sensors in the used anesthesia machine , and absence of anesthesia depth monitors . Keywords: Awareness, recall, general anesthesia.